2007
DOI: 10.1021/cg070320v
|View full text |Cite
|
Sign up to set email alerts
|

Second Ligand-Directed Assembly of Photoluminescent Zn(II) Coordination Frameworks

Abstract: Three new coordination polymers, {[Zn(H2Bpz)(Tph)]·1/2(H2Bpz)} n (1), [Zn 2 (H2Bpz)(Bpz)(Iph)] n (2), and {[Zn 2 (H2Bpz)(HBtc) 2 (H2O) 2 ]·7/6(H2O)} n (3) (H2Bpz = 3,3‘,5,5‘-tetramethyl-4,4‘-bipyrazole; H2Tph = terephthalic acid; H2Iph = isophthalic acid; H3Btc = benzene-1,3,5-tricarboxylic acid), have been isolated from parallel hydrothermal reactions of ZnSO4 and H2Bpz with H2Tph, H2Iph, and H3Btc, respectively. These crystalline solids have been structurally defined, of which 1 was revealed to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…The free bpz display photoluminescence with emission maxima at 331 nm. These peaks originate from the π*→n or π*→π transitions [62,63]. Complex 1 exhibits photoluminescence with an emission maximum at 470 nm, upon excitation at 365 nm at room temperature.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…The free bpz display photoluminescence with emission maxima at 331 nm. These peaks originate from the π*→n or π*→π transitions [62,63]. Complex 1 exhibits photoluminescence with an emission maximum at 470 nm, upon excitation at 365 nm at room temperature.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…[166][167][168] Poly(5,5'-bipyrazole-3,3'-diyl) derivatives 352 were synthesized from 3,3'-dichloro-5,5'-bipyrazoles 347 through dehalogenative polycondensation using a mixture of Ni(cod) 2 and 2,2´-bipyridine in DMF at 60 °C (Scheme 99). The obtained polymers were characterized by their high thermal stability and electrochemical activity.…”
Section: Applications Of Bipyrazolesmentioning
confidence: 99%
“…It was reported that H 2 Bdc acid and {[Zn(H 2 Bpz)(Bdc)]-(H 2 Bpz) 1/2 } n complex exhibited emissions at 382, 470 nm, respectively. 18 However, the luminescence of 3-PyHBIm is unclear, although isomer 4-PyHBIm shows an emission band centered at 492 nm with 370 nm light excitation. 19 We determined the emission bands of 3-PyHBIm under 370, 379 and 383 nm light excitations, which shows a similar emission with a band maximum at 574 nm.…”
Section: Luminescencementioning
confidence: 99%
“…The energy of the luminescence strongly suggests that the emissions of 1 and 2 are Bdc 2-ligand-centered transitions rather than LMCT, especially since Cd(II) and Zn(II) are not oxidizable or reducible ions. 18 …”
Section: Luminescencementioning
confidence: 99%